2018
DOI: 10.15388/infedu.2018.05
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thinking in Primary School: An Examination of Abstraction and Decomposition in Different Age Groups

Abstract: Despite a growing effort to implement computational thinking (CT) skills in primary schools, little research is reported about what CT skills to teach at what age. Therefore, the research questions that guide this study read: (1) How is age related to students' success in computational thinking tasks? (2) How are computational thinking tasks perceived by students? (3) How do students' experience learning with respect to computational thinking? 200 primary school students between the age of 6 and 12 participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 34 publications
2
32
2
2
Order By: Relevance
“…In the current research, it has evident that MR is suitable for developing the concept of Algorithm, 3D pen for Abstraction and OZOBOT for Automation. The results, however, contradict previous study, which indicates the minimum age at which lessons about abstraction is appropriate (Rijke, Bollen, Eysink, & Tolboom, 2018). • CT entails a whole set of mental tools that enable people to represent problems systematically (automation), reduce difficult problems into small solvable small tasks (abstraction) and compose sequence of steps that are executable by a machine (Algorithm) (Chen et al, 2017;Wing, 2006).…”
Section: Automation Petercontrasting
confidence: 62%
“…In the current research, it has evident that MR is suitable for developing the concept of Algorithm, 3D pen for Abstraction and OZOBOT for Automation. The results, however, contradict previous study, which indicates the minimum age at which lessons about abstraction is appropriate (Rijke, Bollen, Eysink, & Tolboom, 2018). • CT entails a whole set of mental tools that enable people to represent problems systematically (automation), reduce difficult problems into small solvable small tasks (abstraction) and compose sequence of steps that are executable by a machine (Algorithm) (Chen et al, 2017;Wing, 2006).…”
Section: Automation Petercontrasting
confidence: 62%
“…Such activities are meant to inspire group work, as well as engaging students as much as possible (Cortina, 2015) This pedagogical strategy is being used in quite a number of countries across the globe, such as in various European countries, the US and Korea (Bell et al, 2009). Several studies were carried out to assess its application, amongst which, Rodriguez, Rader, and Camp (2016) explored the teaching of Computational Thinking concepts in two American middle schools whilst Rijke, Bollen, Eysink, and Tolboom (2018) discussed the introduction of unplugged activities in primary schools. Rodriguez et al concluded that CS unplugged activities increased students' interest in the subject and their level of engagement in class (Rodriguez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, poucas observações foram feitas por parte dos especialistas. Esperávamos que essa prática recebesse boa avaliação, uma vez que ela parece ser consenso entre diversos trabalhos de fomento e avaliação da aquisição do PC [8,16,19,20].…”
Section: Práticasunclassified